Education Landscapes in the 21st Century : Cross-cultural Challenges and Multi-disciplinary Perspectives. - Guske, Iris (Cambridge Scholars Pub., 2008)
With contributions from scholars and practitioners in the fields of education, literacy, literature, media, communication and cultural studies from all five continents, the present volume focuses on themes of pressing importance in today's globalized community. By giving voice to educators committed to excellence in teaching from primary school to university, the book introduces the reader to a plurality of approaches to, and applications of, up-to-date theories in the fields of cognitio ...